Public Service Innovation: Integrated Services Through The Website Of Laweyan Village, Probolinggo District: Inovasi Pelayanan Publik: Pelayanan Terpadu Melalui Website Desa Laweyan Kabupaten Probolinggo - Silvia Jihan Rosyidah; Sabrian Rahma Fadilah; Sheila Puspaningrum; Katerina Bataha (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Laweyan Village operates a village website with the aim of improving service quality and creating a digital village. Villages can make optimal use of information technology. The principles of service provided to the community are comfort, friendliness, politeness, discipline, ease of access, completeness of infrastructure, responsibility, security, accuracy, time certainty, clarity and simplicity. The aim of this activity is to determine the level of technological progress in Laweyan Village and the extent to which the village website is operated. Activities are carried out through mentoring activities in the operation of the village website. The results of the activity are that Laweyan Village has succeeded in operating the village website optimally. With the website, Laweyan Village is a digital village that has made good use of information technology. The existence of a village website has a good impact on the community, makes services easier for the community, and makes the work of the village government easier. The village website can be accessed anytime and anywhere, by all village communities and even all Indonesian citizens.